Upaya Kontingen Garuda II Sebagai Pasukan Perdamaian di Republik Kongo (1960-1961) - Wisnu Arsa Tanjung; Murdiyah Winarti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2022)
The main problem discussed in this article is how the efforts carried out by the Garuda II contingent in the Republic of the Congo. Research methods used used is a historical method which includes several steps, namely heuristics (collecting sources) both oral and written sources, source criticism, interpretation, and historiography. To deepen the analysis, the authors use the approach of the science of sociology, the science of international relations. The research technique used is the study of literature. Based on the results of the research, the Government of Indonesia participated in sending peacekeeping forces to the Republic of Congo under the auspices of the United Nations in 1960. Activities undertaken by the Garuda II Contingent Force namely to overcome and mediate rebellions that occurred in the Republic of Congo and conduct patrols to areas that often occur conflicts such as overcoming the battle of sending Garuda II contingent to the City of Boende and Coquihalville, the battle of Kamina, a mine explosion event in Kamina. From these activities the Garuda II Contingent Forces succeeded in carrying out their duties so as to have a very positive impact on the Indonesian contingent troops so that the following year the Indonesian Government sent the Garuda Contingent back in 1962.Keywords : Battle of Kamina, Garuda troops, Republic of the Congo.AbstrakPermasalahan pokok yang dibahas dalam artikel ini adalah bagaimana usaha-usaha yang dilakukan oleh Kontingen Garuda II di Republik Kongo. Metode penelitian yang digunakan adalah metode historis yang meliputi beberapa langkah, yaitu heuristik baik sumber lisan maupun tulisan, kritik sumber, interpretasi, dan historiografi. Teknik penelitian yang digunakan ialah studi literatur. Berdasarkan hasil peneltian, Pemerintah Indonesia ikutserta dalam pengirimkan pasukan perdamaian ke Republik Kongo dibawah naungan Perserikatan Bangsa-Bangsa pada tahun 1960. Kegiatan-kegiatan yang dilakukan oleh Pasukan Kontingen Garuda II yakni mengatasi dan menengahi pemberontak-pemberontakan yang terjadi di Republik Kongo serta melakukan patroli ke wilayah yang sering terjadi konflik seperti mengatasi pertempuran pengiriman Kontingen Garuda II ke Kota Boende dan Coquihalville, pertempuran Kamina, persitiwa ledakan ranjau di Kamina. Dari kegiatan tersebut Pasukan Kontingen Garuda II berhasil dalam melaksanakan tugas sehingga mendapatkan dampak yang sangat positif bagi pasukan kontingen Indonesia sehingga pada tahun berikutnya Pemerintah Indonesia mengirimkan kembali Kontingen Garuda pada tahun 1962.Kata kunci : Pasukan Garuda, Pertempuran Kamina, Republik Kongo.